Understanding the effect of sodium polyphosphate on improving the chemical stability of Ti3C2Tz MXene in water - Huang, Shuohan; Natu, Varun; Tao, Jingyi; Xia, Yumin; Mochalin, Vadym N.; Barsoum, Michel W. (Journal of Materials Chemistry A, 2022)
Degradation of MXenes in aqueous environments severely limits the application and industrialization of this large family of two-dimensional (2D) materials. Hydrolysis and oxidation are now considered as two main degradation mechanisms and while significant efforts have been directed to prolonging the shelf-life of MXenes, separating and studying their degradation mechanisms have lagged behind. Herein, gas analysis via gas chromatography and Raman spectroscopy were used to investigate the effect of sodium polyphosphate, PP, on the degradation of Ti3C2Tz MXene. Transmission and scanning electron microscopies, as well as X-ray photoelectron spectroscopywere also used as complimentary techniques to support conclusions derived from gas analysis and to confirm the extent of degradation via characterization of solid reaction products. Based on these studies we have determined that the addition of PP to an equal mass of Ti3C2Tz solution can effectively suppress hydrolysis and protect Ti3C2Tz from degradation.